﻿ JEE Mathematics Solved Question Paper 2004 | Previous Year Papers | Zigya

## Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

## Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.

# JEE Mathematics Solved Question Paper 2004

#### Multiple Choice Questions

1.

The number of ways of distributing 8 identical balls in 3 distinct boxes so that none of the boxes is empty is

• 5

• 8C3
• 38

• 21

D.

21

The required number of ways

190 Views

2.

How many ways are there to arrange the letters in the word GARDEN with the vowels in alphabetical order?

• 120

• 480

• 360

• 240

C.

360

A total number of ways in which all letters can be arranged in alphabetical order = 6! There are two vowels in the word GARDEN. A total number of ways in which these two vowels can be arranged = 2!

∴ Total number of required ways

∴ Total number of required ways

186 Views

3.

If a1, a2, a3 , ....,an , .... are in G.P., then the value of the determinant  is

• 0

• -2

• 1

• 2

A.

0

262 Views

4.

If z = x – i y and z1/3 = p+ iq , then  is equal to

• 1

• -2

• 2

• -1

B.

-2

D.

-1

therefore,(Qz = x − iy)
(x - iy) = (p + iq)3
⇒ (x - iy) = p3 +(iq)3 + 3p2qi + 3pq2i2
⇒ (x - iy) = p3 - iq3 + 3p2qi - 3pq2
⇒ (x - iy) = (p3 - 3pq2 ) + i (3p2 q - q3 ) On comparing both sides, we get
⇒ x = (p3 - 3pq2) and - y = 3p2 q - q3
⇒ x = p(p2 - 3q2 ) and y = q(q2 - 3p2 )
421 Views

5.

Let z, w be complex numbers such that z iw + = 0 and arg zw = π. Then arg z equals

• π/4

• 5π/4

• 3π/4

• π/2

C.

3π/4

Since z + iw = 0 ⇒ z = −iw
⇒ z = iw
⇒ w = -iz
Also arg(zw) = π
⇒ arg (-iz2) = π
⇒ arg (-i) + 2 arg(z) = π

956 Views

6.

If one root of the equation x2+px+12 =0 is 4, while the equation x2 +px +q = 0 has equal roots, then the value of 'q' is

• 49/3

• 4

• 3

• 12

A.

49/3

Since 4 is one of the roots of equation x2 + px + 12 = 0. So it must satisfied the equation.
∴ 16 + 4p + 12 = 0
⇒ 4p = -28
⇒ p = -7
The other equation is x2 - 7x + q = 0 whose roots are equal. Let roots are α and α of above equation

⇒ 2α = 7 ⇒ α = 7/ 2 and product of roots α.α = q ⇒ α2 = q

(7/2)2 = q
q =49/4

160 Views

7.

Let two numbers have arithmetic mean 9 and geometric mean 4. Then these numbers are the roots of the quadratic equation

• x2 + 18x +16 = 0

• x2-18x-16 = 0

• x2+18x-16 =0

• x2-18x +16 =0

D.

x2-18x +16 =0

Let α and β be two numbers whose arithmetic mean is 9 and geometric mean is 4.
∴ α + β = 18 ........... (i)
and αβ =16 ........... (ii)
∴ Required equation is x2 - (α + β)x + (αβ) = 0 ⇒ x2 - 18x + 16 = 0 [using equation (i) and equation (ii)]

211 Views

8.

If |z2-1|=|z|2+1, then z lies on

• the real axis

• an ellipse

• a circle

• the imaginary axis

B.

an ellipse

Given that
|z2- 1| = |z|2+ 2
|z2 + (-1)| = |z2| + |-1|
It shows that the origin, -1 and z2 lies on a line and z2 and -1 lies on one side of the origin, therefore
z2 is a negative number. Hence z will be purely imaginary. So we can say that z lies on y-axis.

253 Views

9.

If (1 – p) is a root of quadratic equation x2 +px + (1-p)=0 , then its roots are

• 0, 1

• -1, 2

• 0, -1

• -1, 1

C.

0, -1

Since (1 - p) is the root of quadratic equation
x2 + px + (1 - p) = 0 ........ (i)
So, (1 - p) satisfied the above equation
∴ (1 - p)2 + p(1 - p) + (1 - p) = 0
(1 - p)[1 - p + p + 1] = 0 (1 - p)(2) = 0
⇒ p = 1 On putting this value of p in equation (i)
x2 + x = 0
⇒ x(x + 1) = 0 ⇒ x = 0, -1

190 Views

10.

Let S(K) = 1 +3+5+..... (2K-1) = 3+K2. Then which of the following is true?

• S(1) is correct

• Principle of mathematical induction can be used to prove the formula

• S(K) ≠S(K+1)

• S(K)⇒ S(K+1)

D.

S(K)⇒ S(K+1)

S(K) = 1 + 3 + 5 + ...... + (2K - 1) = 3 + K2
Put K = 1 in both sides
∴ L.H.S = 1 and R.H.S. = 3 + 1 = 4 ⇒ L.H.S. ≠ R.H.S.
Put (K + 1) on both sides in the place of K L.H.S. = 1 + 3 + 5 + .... + (2K - 1) + (2K + 1)
R.H.S. = 3 + (K + 1)2 = 3 + K2 + 2K + 1
Let L.H.S. = R.H.S.
1 + 3 + 5 + ....... + (2K - 1) + (2K + 1) = 3 + K2 + 2K + 1
⇒ 1 + 3 + 5 + ........ + (2K - 1) = 3 + K2 If S(K) is true, then S(K + 1) is also true. Hence, S(K) ⇒ S(K + 1)

158 Views